(untitled) (Communications in Mathematical Research, 2021)
In this paper, we present a general method to prove the complete convergence for arrays of rowwise strong mixing random variables, and give some results on complete convergence under some suitable conditions. Some Marcinkiewicz-Zygmund type strong laws of large numbers are also obtained.